RAB37 Promotes Adipogenic Differentiation of hADSCs via the TIMP1/CD63/Integrin Signaling Pathway - Haili Huang; Anran Li; Jin Li; Dan Sun; Ling Liang; Kunyan Pan; Chengzhang He; Peihua Zhang (Stem Cells International)
The adipogenic differentiation ability of human adipose-derived mesenchymal stem cells (hADSCs) is critical for the construction of tissue engineering adipose, which shows promising applications in plastic surgery and regenerative medicine. RAB37 is a member of the small RabGTPase family and plays a critical role in vesicle trafficking. However, the role of RAB37 in adipogenic differentiation of hADSCs remains unclear. Here, we report that both the mRNA and protein levels of RAB37 fluctuated during adipogenic differentiation. Upregulation of RAB37 was observed at the early stage of adipogenic differentiation, which was accompanied by increased expression of transcription factors PPARγ2 and C/EBPα, and lipoprotein lipase (LPL). Overexpression of RAB37 promoted adipogenesis of hADSCs, as revealed by Oil Red O staining and increased expression of PPARγ2, C/EBPα, and LPL. Several upregulated cytokines related to RAB37-mediated adipogenic differentiation were identified using a cytokine array, including tissue inhibitor of matrix metalloproteinase 1 (TIMP1). ELISA confirmed that upregulation of RAB37 increased the secretion of TIMP1 by hADSCs. Proximity ligation assay showed that RAB37 interacts with TIMP1 directly. Knockdown of TIMP1 compromised RAB37-mediated adipogenic differentiation. In addition, TIMP1 binds membrane receptor CD63 and integrin β1. RAB37 promotes Tyr397 phosphorylation of FAK, an important protein kinase of the integrin β1 signaling. Moreover, both knockdown of CD63 and inhibitor of FAK impeded RAB37-mediated adipogenic differentiation. In conclusion, RAB37 positively regulates adipogenic differentiation of hADSCs via the TIMP1/CD63/integrin β1 signaling pathway.